Pesan Kehidupan Dalam Lirik Lagu Shalawat Bahasa Jawa - Hayati, Nur (SHAHIH: Journal of Islamicate Multidisciplinary, 2018)
This study attempts to reveal meaning of symbols embedded in lyrics of shalawat songs by utilizing semiotics perspective. So far, sholawat is considered as hymne to remind human to God but there is no research about meaning of javanese sholawat songs. This study employs qualitative method to describe the analysis. The analyzed data is based on literature review of the lyrics of sholawat songs. The obtained data is analyzed in semiotic perspective structurally. The result shows us that semiotics is able to reveal meaning of lyrics of javanese sholawat songs. In addition, the results elaborates that lyrics of javanese sholawat songs refer to values of humanity and message of life.